Revisiting media attention score: evolution Of Sin Chew daily’s newspaper design - Jocelyn, Hou Pei Zhi; Faridah Ibrahim,; Chang, Peng Kee (Universiti Kebangsaan Malaysia, 2011)
This study was conducted to revisit media attention score by scrutinizing the evolution of Sin Chew Daily’s newspaper design.The study aims to identify differences in the newspaper design of Sin Chew Daily after the era of independence day up to recent times. Since post-independence, the newspaper is produced using glues and metal, with very simple design. There are differences in terms of the development in layout, headline, column gutters,logo, image, typography and colours from the era of 50’s until now. In this study, the five approaches of Budd attention score are used to measure the news prominence of Sin Chew Daily. The theory in this study is to understand the measurement of visibility and suitability of Budd attention score used in this present day.The purpose of the study is to look at the evolution of Sin Chew Daily’s newspaper design and to review the usage of Budd’s attention score (1964) in evaluating news prominence in Sin Chew Daily.